An investigation into the P13-K/AKT signalling pathway in TNF-a-induced muscle proeolysis in L6 myotubes - Sishi, Balindiwe J. N. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Physiological Sciences))--Stellenbosch University, 2008.